2019
DOI: 10.1073/pnas.1912868116
|View full text |Cite
|
Sign up to set email alerts
|

Rhes, a striatal-enriched protein, promotes mitophagy via Nix

Abstract: Elimination of dysfunctional mitochondria via mitophagy is essential for cell survival and neuronal functions. But, how impaired mitophagy participates in tissue-specific vulnerability in the brain remains unclear. Here, we find that striatal-enriched protein, Rhes, is a critical regulator of mitophagy and striatal vulnerability in brain. In vivo interactome and density fractionation reveal that Rhes coimmunoprecipitates and cosediments with mitochondrial and lysosomal proteins. Live-cell imaging of cultured s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 58 publications
(79 reference statements)
2
41
0
Order By: Relevance
“…In our preliminary findings, we found that Rhes, which promotes mitophagy, can travel via TNT‐like Rhes tunnel to neighboring striatal neuronal cells and interact with damaged mitochondria there. [ 104 ] Thus, TNT‐like Rhes tunnels may be used for the purpose of mitochondrial surveillance. Striatum also consists of two distinct anatomical regions—matrix and striosomes—that are distinguished based on the different neurochemical markers.…”
Section: Rhes‐induced Tnts Have Multiple Roles In Striatal Biology Anmentioning
confidence: 99%
“…In our preliminary findings, we found that Rhes, which promotes mitophagy, can travel via TNT‐like Rhes tunnel to neighboring striatal neuronal cells and interact with damaged mitochondria there. [ 104 ] Thus, TNT‐like Rhes tunnels may be used for the purpose of mitochondrial surveillance. Striatum also consists of two distinct anatomical regions—matrix and striosomes—that are distinguished based on the different neurochemical markers.…”
Section: Rhes‐induced Tnts Have Multiple Roles In Striatal Biology Anmentioning
confidence: 99%
“…Our study demonstrates that Rhes requires the mitophagy receptor NIX to clear damaged mitochondria [73]. In cells that lack the NIX receptor, the Rhes protein fails to induce mitophagy.…”
Section: Rhes May Act As a Mitophagy Ligand Via Nix To Induce Mitophagymentioning
confidence: 67%
“…We found that Rhes is a potent inducer of cellular protrusion (Rhes tunnel) and transports endosomes and lysosomes, but not mitochondria, to the neighboring cells; however, we found that Rhes specially associates with the damaged mitochondria in the neighboring cells via NIX [73,85]. This indicates that Rhes has the capacity of intercellular mitochondrial surveillance in vitro.…”
Section: Rhes As An Intercellular Mitochondrial Surveillant In 3-np-imentioning
confidence: 69%
See 2 more Smart Citations